STRATEGI MANAJEMEN SDM TERHADAP PENINGKATAN KUALITAS PELAYANAN KARYAWAN DI KANTOR CAMAT MEDAN PETISAH - Anita Bersama Sihombing; Dhita Adriani Rangkuti; Grace Cia Nainggolan; Dona Agreachi Br Sitepu; Windi Theresia Br Bangun; Andrew Satria Lubis (POLITEKNIK LP3I JAKARTA, 2025)
This study was conducted to see the results of HR management strategies on improving the quality of employee services at the Medan Petisah District Office. Improving the quality of public services is one important aspect in efforts to increase public trust in the sub-district government office as a government institution. There needs to be a management strategy in human resources to be able to improve the quality of good service. The population of this study was 68 employees and the entire population was used as a sample. The approach to this study is based on a quantitative descriptive approach and uses multiple linear regression analysis as a test in this study with simultaneous results, then Training, Coaching, Recruitment have a positive and significant effect on the service quality variable at the Medan Petisah District Office